2016
DOI: 10.1002/jmor.20510
|View full text |Cite
|
Sign up to set email alerts
|

Baleen wear reveals intraoral water flow patterns of mysticete filter feeding

Abstract: A survey of macroscopic and microscopic wear patterns in the baleen of eight whale species (Cetacea: Mysticeti) discloses structural, functional, and life history properties of this neomorphic keratinous tissue, including evidence of intraoral water flow patterns involved in filter feeding. All baleen demonstrates wear, particularly on its medial and ventral edges, as flat outer layers of cortical keratin erode to reveal horn tubes, also of keratin, which emerge as hair-like fringes. This study quantified five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…D–F). This unusual phenomenon has been documented (Werth et al, ), but the widespread extent of its nature was not known until numerous specimens of nearly all balaenopterid species were examined for this study. Laterally projecting baleen fringes at this location are visible not only in post mortem exams but also in full or partial baleen racks in museum collections.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…D–F). This unusual phenomenon has been documented (Werth et al, ), but the widespread extent of its nature was not known until numerous specimens of nearly all balaenopterid species were examined for this study. Laterally projecting baleen fringes at this location are visible not only in post mortem exams but also in full or partial baleen racks in museum collections.…”
Section: Resultsmentioning
confidence: 95%
“…It is widely known that every rorqual species possesses 180–400 triangular plates or laminae of baleen in each of two paired racks (Young et al, ). A recent study of wear patterns (Werth et al, ) has shown that baleen fringes (also called bristles, hairs, filaments, or fibers) frequently (40%–60% of the time) are redirected by consistent intraoral water flow patterns, and that the orientation of the fringes, and microscopic scuff marks on the baleen fringes and plates, reveals directions of water flow. In further examining baleen's fringe orientations and related structural arrangement for this project, we found, additionally, that there are markedly distinct patterns of fringe orientation evident in the baleen racks of rorquals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initial microscopic analysis [14] indicates a scuffed, scale-like surface in dried baleen, as tiny, cuticle-like keratin plates form a rough, ridged exterior. Pfeiffer [34] noted this in baleen fringes, but it has not yet been thoroughly described in a survey of baleen plates.…”
Section: Resultsmentioning
confidence: 99%
“…The role of anisotropy in resisting crack propagation in mammalian keratin has been explored [47]. In life, such failure would merely promote the erosive wear process that reveals the horn tubes [14], which when exposed form the crucial fringes that perform most of the work of filtration for feeding, especially in balaenid (right and bowhead) whales [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Curvature may be important not only for understanding the drag production by those hydrofoils, but also the lift that they may also produce (more energy dissipation) and the possible baleen-tip bending and movement that could follow. The latter would help further understand the wear patterns of baleen [39]. Finally, more work will be needed to clarify the role of the tongue’s shape and bulk within the oral apparatus.…”
Section: Discussionmentioning
confidence: 99%